A collagen scaffold loaded with human umbilical cord-derived mesenchymal stem cells facilitates endometrial regeneration and restores fertility. (1st July 2019) - Xin, Liaobing; Lin, Xiaona; Pan, Yibin; Zheng, Xiaowen; Shi, Libing; Zhang, Yanling; Ma, Lie; Gao, Changyou; Zhang, Songying
Graphical abstract: Abstract: In women of reproductive age, severe injuries to the endometrium are often accompanied by endometrial scar formation or intrauterine adhesions (IUAs), which can result in infertility or miscarriage. Although many approaches have been used to treat severe IUAs, high recurrence rates and endometrial thinning have limited therapeutic efficiency. In this study, a collagen scaffold (CS) loaded with human umbilical cord-derived mesenchymal stem cells (UC-MSCs) was fabricated and applied for endometrial regeneration. The CS/UC-MSCs promoted human endometrial stromal cell proliferation and inhibited apoptosis in vitro through paracrine effects. In a model of endometrial damage, transplantation with the CS/UC-MSCs maintained normal luminal structure, promoted endometrial regeneration and collagen remodeling, induced intrinsic endometrial cell proliferation and epithelium recovery, and enhanced the expression of estrogen receptor α and progesterone receptor. An improved ability of the regenerated endometrium to receive embryos was confirmed. Together, our results indicate that the CS/UC-MSCs promoted endometrial structural reconstruction and functional recovery. Topical administration of the CS/UC-MSCs after trans -cervical resection of adhesions might prevent re-adhesion, promote endometrium regeneration and improve pregnancy outcomes for patients with severe IUAs. Statement of Significance: Intrauterine adhesions due to severe endometrium injuries happen frequently in clinic and become one of the crucial reasons for women's infertility or miscarriage. Therefore, how to regenerate the damaged endometrium is a big challenge. In this study, a collagen scaffold (CS) loaded with human umbilical cord-derived mesenchymal stem cells (UC-MSCs) was fabricated and applied for endometrium regeneration. Herein, UC-MSCs, known for low immunogenicity and high proliferative potential, exhibit promising potential for endometrium regeneration; and collagen scaffolds provide suitable physical support. It was proved that transplantation with CS/UC-MSCs promoted endometrial regeneration and fertility restoration. It suggested that topical administration of CS/UC-MSCs in uterus could be a promising strategy for patients suffering severe intrauterine adhesion and infertility.